A DFT study of mechanical properties, thermal conductivity and electronic structures of Th-doped Gd2Zr2O7. (December 2016) - Zhao, F.A.; Xiao, H.Y.; Liu, Z.J.; Li, Sean; Zu, X.T.
Abstract: A systematic density functional theory study is performed to investigate the mechanical stability, elastic moduli, Debye temperature, thermal conductivity and electronic structures of Gd2- y Th y Zr2 O7 and Gd2 Zr2- y Th y O7 . All the Th-doped Gd2 Zr2 O7 compositions are found to be structurally and mechanically stable. As compared with the pure Gd2 Zr2 O7, Th incorporation into both Gd-site and Zr-site results in generally better ductility, lower Debye temperature, and reduced thermal conductivity. The reduction in thermal conductivity can be as high as 25–32%, depending on the content of the Th substituent. Our calculations suggest that Th-doped Gd2 Zr2 O7, especially Gd2 Zr2- y Th y O7, exhibits better mechanical and thermal properties that are beneficial to its application as thermal barrier coating material at high temperatures than the pure state. Graphical abstract: